Employees propensity for emotional contagion as a mediating variable between job satisfaction and perceptions of customers’ mood: a comparative case study - Rueff-Lopes, Rita; Planella, Elisabeth; Pendleton, Ann (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Particularly directed to customer service organizations and specifically focused on frontline employees, this research explores how the relation between employees’ perceptions of customers’ mood and job satisfaction can be mediated by their levels of emotional contagion. We conducted a comparative case study contrasting two conditions of service encounters: telephone and face-to-face. According to our hypotheses, results support a positive correlation between job satisfaction and perceptions of customers’ mood. However, the mediating role of employees’ levels for emotional contagion is only present on the face-to-face interaction group. We suggest that emotional contagion is stronger where all the resources of mood influence and exchange are present (proxemics, kinesics and paralinguistic). In such work settings the emotional contagion scale (Doherty, 1997) could and should be used as a selection tool. For job environments where workers are not exposed to visual contact, further investigation is needed in order to understand how the emotional exchange flows between customers and employees.